2023
DOI: 10.1038/s42003-023-05442-5
|View full text |Cite
|
Sign up to set email alerts
|

Corvids optimize working memory by categorizing continuous stimuli

Aylin Apostel,
Matthew Panichello,
Timothy J. Buschman
et al.

Abstract: Working memory (WM) is a crucial element of the higher cognition of primates and corvid songbirds. Despite its importance, WM has a severely limited capacity and is vulnerable to noise. In primates, attractor dynamics mitigate the effect of noise by discretizing continuous information. Yet, it remains unclear whether similar dynamics are seen in avian brains. Here, we show jackdaws (Corvus monedula) have similar behavioral biases as humans; memories are less precise and more biased as memory demands increase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Indeed, increasing evidence has shown that this robust representation in higher-level cortex is useful particularly under high memory loads (Christophel et al, 2017;Linden et al, 2003;Xu & Chun, 2006), or during interference (Bettencourt & Xu, 2016). This is possibly because when storing precise, detailed information in VWM becomes (Panichello et al, 2019), but also in primates (Freedman et al, 2001, Panichello et al, 2019 and corvid (Apostel et al, 2023). The attractor dynamics model (Almeida et al, 2015;Panichello et al, 2019) suggests that as memory load increases, internal noise of memory errors (or "random diffusion") increases, while VWM is more biased towards certain nearby locations (or "attractors"), such as color prototypes (Bae et al, 2015;Zhou et al, 2021) and cardinal orientations (Bae, 2021).…”
Section: Working Memory Storage Is Supported By Multiple Brain Areas ...mentioning
confidence: 99%
“…Indeed, increasing evidence has shown that this robust representation in higher-level cortex is useful particularly under high memory loads (Christophel et al, 2017;Linden et al, 2003;Xu & Chun, 2006), or during interference (Bettencourt & Xu, 2016). This is possibly because when storing precise, detailed information in VWM becomes (Panichello et al, 2019), but also in primates (Freedman et al, 2001, Panichello et al, 2019 and corvid (Apostel et al, 2023). The attractor dynamics model (Almeida et al, 2015;Panichello et al, 2019) suggests that as memory load increases, internal noise of memory errors (or "random diffusion") increases, while VWM is more biased towards certain nearby locations (or "attractors"), such as color prototypes (Bae et al, 2015;Zhou et al, 2021) and cardinal orientations (Bae, 2021).…”
Section: Working Memory Storage Is Supported By Multiple Brain Areas ...mentioning
confidence: 99%